2016
DOI: 10.1038/srep22403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonication on increased germination and improved seedling growth of aged grass seeds of tall fescue and Russian wildrye

Abstract: The effects of ultrasonic treatments on the germination and seedling growth of aged tall fescue (Festuca arundinacea) and Russian wild rye (Psathyrostaehys juncea Nevski) seeds were determined using orthogonal matrix experimental design with four ultrasonic factors. The multivariate analysis of variance detected significant differences and coupling effects of the pair-wise factors. The activities of Superoxide Dismutase (SOD) and Peroxidase (POD) and the Malondialdehyde (MDA) content were affected. The ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 48 publications
1
60
1
1
Order By: Relevance
“…Therefore, ultrasound could have improved those processes for mung bean, helping the reserve molecules catabolism and the transport of molecules to the radicle (mass transfer improvement), reducing the stage II duration. In fact, Liu et al 43,. demonstrated that the ultrasound technology increased the metabolic activity of aged grass seed, enhancing the germination percentage, attributing this improvement to the cited reasons and the increment of the porosity of the seed by the acoustic cavitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ultrasound could have improved those processes for mung bean, helping the reserve molecules catabolism and the transport of molecules to the radicle (mass transfer improvement), reducing the stage II duration. In fact, Liu et al 43,. demonstrated that the ultrasound technology increased the metabolic activity of aged grass seed, enhancing the germination percentage, attributing this improvement to the cited reasons and the increment of the porosity of the seed by the acoustic cavitation.…”
Section: Resultsmentioning
confidence: 99%
“…3a and b), causing the bean germination, leading to the stage III. In fact, the ultrasound technology has improved the germination process of other seeds, such as barley3940, switchgrass41, pea42 and grass seeds43. Most of those works gave as the possible effect of ultrasound on the germination process, the increasing in the nutrient mobility, the respiration rate and/or the water availability for metabolic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the effect of ultrasound, this technology is well referenced due to its capacity to improve germination. In fact, many works have reported this improvement for different seeds and grains, such as chickpeas, wheat and pepper (Goussous, Samarah, Alqudah, & Othman, ), barley kernels (Miano et al., ), rice kernels (Ding et al., ), mung beans (Miano et al., ), grass seeds (Liu et al., ), and red rice (Ding et al., ). The main attributed mechanisms of this improvement reported in those published works are the acceleration of mass transfer (water, gases, and nutrients) and the acceleration of metabolism by the activation of enzymes, the acceleration of nutrients mobilization, or other physiological effect.…”
Section: Resultsmentioning
confidence: 99%
“…Acoustic waves with higher frequencies are known as ultrasounds (>20 kHz). Ultrasounds have been successfully used as a priming technique in seeds of different species [711]. However, long ultrasound treatments may have negative effect in germination and induce mutagenesis [12] and the optimum ultrasound dosis may vary depending on the device used and seed type.…”
Section: Introductionmentioning
confidence: 99%